Poor concordance between reason for consultation and parental expectations in behavioral referrals. (18th May 2018) - Gander, Sarah; Campbell, Sarah; Borodovski, Andrew
Abstract: BACKGROUND: Behavioural conditions such as Attention-deficit/hyperactivity disorder (ADHD) are present in up to 5% of children across the world. This is a common reason for referral from primary care to paediatricians. When a primary care provider refers a patient to a specialist, they often create a set of expectations in the patient. These expectations may have a strong effect on the patient relationship with the specialist. It has been shown that parental expectations can influence prescribing practices in paediatrics. Low socioeconomic status, a risk factor for behavioural conditions is also a risk factor for poor physician-patient communication. If patient expectations set up in primary care are not reflected in the referral question sent to the paediatrician, this may hinder paediatrician-patient communication and impact care. OBJECTIVES: The primary objective of this project was to determine the level of concordance between physician referrals and parent expectations in the consultant paediatrician's office. A secondary objective was to examine demographic and socio-economic trends within this population. DESIGN/METHODS: A clinic nurse conducted almost 500 pre-appointment intake interviews of guardians in children with a referral related to a behavioural concern and asked them their expectations for the consultation. The referral question and parental expectations were categorized by question of behavioural diagnosis, learning difficulties, medical complaint or unknown. Chi sqaured analysis was performed to measure concordance. RESULTS: Among this population, 70.4% were male, with 54% coming from single parent families. Chi-square analysis indicated a small-moderate level of concordance on issues relating to attention, behaviour and academics, (59.9%, p<0.001; 57.3%, p<0.001; 62.6%, p=0.001), and high concordance but low correlation for social and medical issues (80.1%, p=0.002, 91.6%, p=0.06). CONCLUSION: This study demonstrates how we could improve our patient-centered approach by being clear in what is being offered by paediatric consultation. When primary care providers consult paediatrics for behavior referrals there should be clear commnication of the concern at hand and management of the expectations for the visit with the family. This will improve efficiency and lessen dealys or barriers to access to care allowing approriate triage of referrals and patient satisfaction.